OUTCRY AND CALL FOR RELIEF: EXPERIENCES AND SUPPORT NEEDS OF PARENTS WITH NYAOPE USERS - Masombuka, Jan; Qalinge, Lulama (Social Work/Maatskaplike Werk, 2020)
The abuse of nyaope as a recent drug added to the market continues to increase at an alarming rate. This drug is causing devastation in previously designated Black townships. The negative consequences of this phenomenon affect users and their parents. This qualitative study looked at the experiences and support needs of parents of nyaope users. Eight parents of nyaope users were interviewed using semi-structured face-to-face interviews. Purposive sampling was used to choose participants. The findings indicate that parents of nyaope users are overwhelmed and cry out for professional help. This study recommends that therapeutic interventions be extended to parents of nyaope users.